2007
DOI: 10.1038/sj.onc.1210386
|View full text |Cite
|
Sign up to set email alerts
|

Id3 is a novel regulator of p27kip1 mRNA in early G1 phase and is required for cell-cycle progression

Abstract: P27kip is a key inhibitory protein of the cell-cycle progression, which is rapidly downregulated in early G1 phase by a post-translational mechanism involving the proteosomal degradation. In this study, using a wounding model that induces cell-cycle entry of human dermal fibroblasts, we demonstrate that p27mRNA is downregulated when cells progress into the G1 phase, and then it returns to its basal level when cells approach the S phase. By using a quantitative polymerase chain reaction screening we identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 50 publications
1
27
0
Order By: Relevance
“…This may explain the 13I effect on SH-EP cells, at least partly, as E47 activity prevents cell cycle progression in neuroblastoma cells (Rothschild et al, 2006). Finally, 13I affected the expression of the Id targets p27 kip1 and VEGF (Lasorella et al, 2005;Chassot et al, 2007), by turning the first on and the second off. Such a deregulation was reversed by over-producing ID2.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This may explain the 13I effect on SH-EP cells, at least partly, as E47 activity prevents cell cycle progression in neuroblastoma cells (Rothschild et al, 2006). Finally, 13I affected the expression of the Id targets p27 kip1 and VEGF (Lasorella et al, 2005;Chassot et al, 2007), by turning the first on and the second off. Such a deregulation was reversed by over-producing ID2.…”
Section: Discussionmentioning
confidence: 98%
“…Through the HLH domain, Ids associate with the ubiquitous bHLHs, the E proteins, preventing DNA binding and complex formation with tissue-specific bHLHs (Ruzinova and Benezra, 2003). They also interact with non-bHLH proteins such as PAX, ETS, ELK and underphosphorylated RB (Iavarone et al, 1994;Ohtani et al, 2001;Roberts et al, 2001;Chassot et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…[56][57][58] Conversely, Id knockdown is associated in many cell types with increased expression of CDKIs. 53,56,[59][60][61][62][63] Recently we reported that E47 directly activates p57…”
Section: Discussionmentioning
confidence: 99%
“…Using a wounding model as an inducer of cell cycle entry for human dermal fibroblasts, when Id3 was silenced, the expected down-regulation of p27 did not occurred, suggesting that transcription repression of p27 was regulated by Id3. It was also found that both G1 phase progression and G1/S transition were blocked by Id3 depletion (14).…”
Section: Effect Of Id3 Suppression On the Sensitivity Of Cancer Cellsmentioning
confidence: 89%
“…These inhibitors sequestrate CDKs and therefore stop them from phosphorylating pRB, hence having an indirect anti-proliferation effect (13). Id3 specifically regulates P27 through an ETS domain factor called ELK1 (14). Id1 and Id3 have also been identified as downstream targets of MYC (15).…”
Section: Introductionmentioning
confidence: 99%